DETERMINAN PENINGKATAN KINERJA KARYAWAN PADA KANTOR BPJS KETENAGAKERJAAN CABANG MEDAN - Waruwu Ahmad Aswan; Anjali Aina (STAI Syekh.H. Abdul Halim Hasan Al Ishlahiyah Binjai, 2022)
This study aims to examine and determine how the influence of individual characteristics, workload and work environment partially and jointly on employee performance at BPJS Ketenagakerjaan Medan Branch. This study uses quantitative methods involving 49 respondents. Data was collected by using questionnaires for each sample. Then the data obtained were analyzed using statistical formulas, namely by using multiple linear regression analysis whose processing was carried out with the SPSS Version 16.0 program. Based on the results of the study showed that individual characteristics partially had no positive and insignificant effect on employee performance, workload partially had no positive and insignificant effect on employee performance and the work environment partially had a positive and significant effect on employee performance. Individual characteristics, workload and work environment together have a positive and significant effect on employee performance at BPJS Ketenagakerjaan Medan Branch. With the results of this study, the management of BPJS Ketenagakerjaan Medan Branch needs to pay more attention, especially with regard to the work environment, while individual characteristics and workloads need to be maintained with current achievements.